1988
DOI: 10.3109/02844318809097941
|View full text |Cite
|
Sign up to set email alerts
|

Hand Function After Replantation or Revascularization of Upper Extremity Injuries:A Follow-Up Study of 21 Cases Operated on 1979–1985 in Göteborg

Abstract: Twenty-one patients with revascularized/replanted amputated parts of the upper limb were studied for an evaluation of hand function. Two patients had been injured at the lower arm to wrist level, four between the wrist and MCP joint, three distal to the MCP joints in thumbs and/or fingers, and twelve in the thumb only. Hand function was measured as grip and pinch strength, range of movement (ROM), sensibility (two point discrimination), and Sollerman test score. Cold sensitivity as related to circulatory chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 8 publications
2
28
0
Order By: Relevance
“…This was noted by Blomgren et al (1998), who obtained the best functional results after replantation of thumbs, although the active range of motion of replanted/revascularised thumbs in this study was only 19% of the active range of motion of the contralateral thumbs. Urbaniak et al (1985) reported an average active range of motion of 351 (13% of the contralateral digit) after single digit replantation at the level proximally to the FDS insertion and a mean active range of motion of 821 (30% of the contralateral digit) after replantation distal to FDS insertion.…”
Section: Discussionsupporting
confidence: 42%
“…This was noted by Blomgren et al (1998), who obtained the best functional results after replantation of thumbs, although the active range of motion of replanted/revascularised thumbs in this study was only 19% of the active range of motion of the contralateral thumbs. Urbaniak et al (1985) reported an average active range of motion of 351 (13% of the contralateral digit) after single digit replantation at the level proximally to the FDS insertion and a mean active range of motion of 821 (30% of the contralateral digit) after replantation distal to FDS insertion.…”
Section: Discussionsupporting
confidence: 42%
“…The Sollerman test has been used to evaluate hand function in tetraplegia, gout, and after hand trauma. [12,18,51] It has a good intra-and inter rater reliability when used in patients with chronic stroke. [13] Aims To describe the epidemiology of hand injury from powered wood splitters.…”
Section: Hand Injury Severity Scoring Systemmentioning
confidence: 99%
“…Traumatic amputation of a thumb is an absolute indication for replantation since the functional and aesthetic results of a successfully replanted thumb are better than those obtained by other available Many systems for evaluation of hand function after replantation of digits have been proposed. 3- 6 Burton stated that any system of evaluation for reattachment surgery must be multifactorial .7 Evaluation of late results and comparing different series after replantation of multiple digits often combined with other injuries on the ipsilateral or contralateral side is difficult. This series of 46 patients with isolated thumb replantation presented here is rather more uniform than usual.…”
Section: Microsurgery 17:26and267 1996mentioning
confidence: 99%